Latin American documentary cinema. Conclusions based on a cross-sectional study with contextual and formal orientation of 100 documentary films [Cine documental latinoamericano. Conclusiones con base en un estudio trasversal con enfoque contextual y formal de 100 películas documentales] (2019)
This article is the result of a broad-spectrum research, the result of a doctoral thesis. The research wants to see if you can really talk about a Latin American documentary today. To answer this question, a cross-sectional study of the contributions to the field of documentary of the most relevant cinematographies in the region-in terms of production volume and the importance of their titles-is done. In addition, those significant contributions arising from minority contexts are taken into consideration. At the methodological level, the present study considers three aspects. A qualitative analysis that takes into account the evolution of gender in Latin America at the regional level, the formal aspects derived from technical advances and the production context in which the films analyzed are produced. The last two aspects will condition the configuration of a language with common features. © 2019 Universidad de Caldas. All rights reserved.